Kodeks honorowy w Wojsku Polskim III RP - Ossowski, Szymon (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2004)
The political transformation in Poland at the turn of the eighties also affected the military. One of the aspects of this transformation was an attempt at creating a code of honor for the soldiers of a „renewed” Polish Army, undertaken at the beginning of the nineties. Unfortunately, the work on the Code of Honor for the Polish Army of the 3rd Republic has not been finalized. Although a few drafts of varied merit have been drawn up, there has been no sufficient political will to eventually effect this interesting and noteworthy project. Maybe some have also feared that the professional soldiers equipped with the Code of Honor will become too independent and courts of honor will practically depreciate the significance of military courts. Also, nearly all the documents devoted to this matter at that time reflect the intention to develop the code, yet they lack assuredness of what its character should be. Therefore, the main points of focus were general rules referring to morality and conduct, while definitely too little attention was paid to practical suggestions and solutions.